Analysis of direct and indirect selection and indices in soybean segregating populations - Costa, Marcelo Marchi; Di Mauro, Antonio Orlando [UNESP]; Unêda-Trevisoli, Sandra Helena; Arriel, Nair Helena Castro; Bárbaro, Ivana Marino; Da Silveira, Gustavo Dias; Muniz, Franco Romero Silva [UNESP] (My University, 2008)
Estimates of gain with selection are very useful in breeding programs to predict the success of selection. Index-based simultaneous selection makes breeding more successful. The objective of this report was to estimate and compare the genetic gain obtained by direct and indirect selection and using the classical and based on desired gain indices. The experiment was set up in the design of families with intercalated checks with 293 F3 soybean genotypes, distributed in 32 families derived from five crosses. Individual gains obtained with direct selection among and within families and mass selection were similar and in most cases higher than selection by indices. On the other hand, the highest total gains were obtained with selection indices and distributed across all traits. The classical index obtained the highest genetic gains.
Keywords: Expected gain; Glycine max; Selection among and within families; Selection indices